Active learning theory towards the use of e-learning / Rozita Kadar... [et al.] - Kadar, Rozita; Umar, Norazah; Othman, Jamal; Ahmad, Nurhafizah (Unit Penerbitan JSKM, 2020)
Teaching can be based in or out of the classrooms enabled to transfer of skills and knowledge. Now a days, most of universities have implementing e-learning method to enhance the traditional form of teaching and this method gives students much greater flexibility of study (Diana, 2005). The e-learning system based on formalized teaching but with the help of electronic resources which is utilizing the electronic media, and information and communication technologies. The use of computers and the Internet forms the major component of e-learning. It includes numerous types of media that deliver text, audio, images, animation, and streaming video, and includes technology applications and processes such as audio or video tape, satellite TV, CD-ROM, as well as local intranet/extranet. There are different approaches in implementing e-learning. Algahtani (2011) discovers three distinct approaches of using e-learning in education which are: adjunct, blended and online. Figure 1 shows the model of approaches using e-learning in education.